Dimensi Tasawuf dalam Musik Religi Bimbo, 1974-1980: Sebuah Kajian Sejarah - Yuda Adi Pradana; Imas Emalia (Buletin Al-Turas, 2020)
This article discusses Islamic da'wa delivered through music with its song lyrics. The purpose of this study is to uncover Islamic da'wa in Bimbo songs. Bimbo's type of music is categorized as seasonal music which is only popular at certain times, especially the month of Ramadan. The research used a historical approach to uncover the development of Bimbo songs, and a semantic approach is also used to analyze the meaning and Sufism message contained in their song lyrics. Based on data analysis conducted, it is known that in Indonesia, Bimbo was a music group established in Bandung in 1974 that pioneered religious music and songs. Bimbo started its career through pop music with love, politic, environment, and humor themes. For six years, the Bimbo music group has sung more than 50 songs adopted from Taufiq Ismail 's Islamic poetry some of which were about Sufism. The theme of Sufism in Bimbo songs illustrates the deep inspiration of the singer and creator so that it becomes separate preaching that is easily accepted by the community. It can be concluded that Bimbo, the religious music group was famous for its musical character and Islamic poetry which contains the Sufiems values. Artikel ini membahas tentang tema tasawuf sebagai dakwah Islam yang disampaikan melalui seni musik dalam syair-syair lagu. Tujuan penelitian ini adalah untuk mengungkap dakwah Islam dalam lagu-lagu Bimbo. Jenis musik Bimbo dikategorikan sebagai musik musiman yang hanya populer pada saat-saat tertentu, khususnya bulan Romadhan.  Pendekatan yang digunakan dalam penelitian ini adalah pendekatan sejarah untuk mengungkap perkembangan lagu-lagu Bimbo. Pendekatan semantik juga digunakan untuk menganalisis makna dan pesan tasawwuf dalam lagu Bimbo. Berdasarkan analisis data yang dilakukan, diketahui bahwa di Indonesia, musik religi Islam dipelopori oleh kelompok musik Bimbo asal Bandung pada 1974. Bimbo mengawali kariernya melalui musik pop yang bertemakan cinta, politik, lingkungan, dan humor atau jenaka. Selama enam tahun kelompok musik Bimbo telah menyanyikan lagu dengan syair islami karya Taufiq Ismail sekitar lebih dari 50-an lagu, bahkan ada yang bertemakan tasawuf. Tema tasawuf dalam lagu-lagu Bimbo menggambarkan penjiwaan yang dalam pada penyanyi dan penciptanya sehingga menjadi dakwah tersendiri yang mudah diterima di kalangan masyarakat. Dengan demikian dapat disimpulkan bahwa kelompok musik religi Bimbo terkenal dengan karakter musik dan syair islami yang mengandung nilai-nilai tasawuf. يناقش هذا البحث الدعوة الإسلامية التي يتم تقديمها من خلال فن الموسيقى في نصوص الأغاني. و الغرض من هذه الدراسة كشف الدعوة الإسلامية في أغاني بيمبو(Bimbo). أغاني بيمبو(Bimbo)   موسيقى مؤقتة تحظى بشعبية كبيرة في أوقات معينة فقط، خاصة في شهر رمضان. و الطريقة المستخدمة في هذا البحث هي الطريقة التاريخية و الدلالية. استنادًا إلى تحليل البيانات الذي تم إجراؤه، من المعروف أن الموسيقى الدينية الإسلامية في إندونيسيا كانت رائدة في مجموعة Bimbo الموسيقية من باندونج في عام 1974. بدأ Bimbo مسيرته المهنية من خلال موسيقى البوب (Musik Pop) بعنوان: الحب، والسياسة، والبيئة، والفكاهة. على مدار ست سنوات، غنت مجموعة بيمبو الموسيقية أغاني الشعر الإسلامي يؤلف توفيق إسماعيل أكثر من 50 أغنية، و أن هناك الأغاني بالموضوعات الصوفية. و يوضح الموضوع الصوفي في أغنيات Bimbo الإلهام العميق للمغني والمبدع بحيث يصبح عظة منفصلة يتم قبولها بسهولة في المجتمع. لذلك، استنتج الباحث أن مجموعة بمبو(Bimbo) الموسيقية الدينية تشتهر بطابعها الموسيقي والشعر الإسلامي الذي يحتوي على القيم الصوفية ويؤثرعلى تطور الموسيقى في إندونيسيا أيضا.